ELEVATED INTERLEUKIN-6 AND COTININE LEVELS FOLLOWING ELECTRONIC CIGARETTE EXPOSURE: STUDY IN VIVO - Rahma, Aline Febridha; Parmasari, Wahyuni Dyah; Margaretha Sutandio, Yunitati Maria; Sanjaya, Ayling (FKG ULM, 2026)
Background: Periodontitis is a chronic inflammatory disease affecting the supporting tissues of the teeth. Animal models are commonly used to study its pathogenesis and the effects of various exposures. E-cigarette vapor contains nicotine and other harmful substances that may induce inflammation. Cotinine and interleukin-6 (IL-6) serve as biomarkers of nicotine exposure and inflammatory response. Purpose: This study aimed to evaluate cotinine and IL-6 levels in Wistar rats exposed to e-cigarette vapor and to assess the relationship between nicotine exposure and systemic inflammation in periodontitis. Methods: Twelve Wistar rats were divided into treatment and control groups. The treatment group was exposed to e-cigarette vapor for 35 days (30 puffs/day), while the control group received no exposure. Cotinine and IL-6 levels were measured using Enzyme-Linked Immunosorbent Assay (ELISA). Independent t-tests and Pearson correlation analyses were performed. Results : The treatment group exposed to e-cigarette vapor showed higher IL-6 and cotinine levels compared to the control group. The mean for IL-6 was 27,5 pg/mL (treatment group) and 13,8 pg/mL (control group), while for cotinine it was 227,6 ng/mL (treatment group) and 175,4 ng/mL (control group). A positive correlation was observed (r = 0.515; p = 0.086), although this did not reach statistical significance. Conclusion: E-cigarette vapor exposure increased cotinine and IL-6 levels in Wistar rats, indicating enhanced systemic inflammation. However, these findings should be interpreted with caution due to the small sample size and animal model. Further studies involving larger samples and human subjects are needed to confirm these results and determine their clinical relevance.Keywords: Cotinine, Electronic_Cigarette, Interleukin-6, Periodontitis